Силы Казимира в моделях с нетривиальной топологией - Т. Ш. Навасардян; А. А. Саарян (ՀՀ ԳԱԱ հրատ.)
For a scalar field the Casimir forces, acting on parallel plates in models with a compact subspace, are investigated. On the plates the field obeys the Robin boundary conditions. Depending on the values of the coefficients in the boundary conditions, the forces can be either attractive or repulsive. In models with a homogeneous compact subspace they are the same for both the plates. In special cases of Dirichlet and Neumann boundary conditions the Casimir forces are attractive. As applications of general results, we consider special cases with the subspaces S1 and S2.
Keywords: Physics; Science; Nuclear Physics; Quantum Physics